3,4,5-Trihydroxy-N '-(2-hydroxy-5-nitrobenzylidene)benzohydrazide monohydrate - Alhadi, A.A.A.; Ng, S.W.; Ali, Hapipah Mohd (International Union of Crystallography, 2009)
The benzohydrazide molecule of the title compound, C(14)H(11)N(3)O(7)center dot H(2)O, is planar (r.m.s. deviation = 0.068 angstrom). The benzohydrazide molecule and the uncoordinated water molecule interact through O-H center dot center dot center dot O hydrogen bonds; these together with O-H center dot center dot center dot N and N-H center dot center dot center dot O hydrogen bonds form a three-dimensional network.